2014
DOI: 10.7314/apjcp.2014.15.11.4571
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes - Increased Risk for Cancers through Chromosomal Aberrations?

Abstract: Diabetes, a comprehensive genetic disease, is principally due to the deregulation of glucose levels in the blood. In addition to contemporary epidemiological studies, systematic substantiation suggests that long-term diabetes leads to cancers due to a variety of reasons. In this study, blood samples were collected with informed consent from confirmed type I diabetic (T1DM, n=25) and type II Diabetic patients (T2DM, n=25) with equal numbers of controls. Further depending on the lifestyle habits they were subdiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
3
5
0
1
Order By: Relevance
“…In addition, in cells from diabetic patients an impaired DNA repair, combined to a weakened antioxidant defense, contributes to enhance DNA damage ( Blasiak et al, 2004 ). Consistently, oxidative damage and DNA strand breaks have been found in both type 1 and type 2 diabetic patients ( Goodarzi et al, 2010 ; Tatsch et al, 2012 ; Anand et al, 2014 ). We have recently shown in Drosophila that PLP deficiency can further increase DNA damage in cells from diabetic individuals ( Merigliano et al, 2018 ).…”
Section: Plp Depletion As New Cancer Risk Factor In Diabetic Cellssupporting
confidence: 52%
“…In addition, in cells from diabetic patients an impaired DNA repair, combined to a weakened antioxidant defense, contributes to enhance DNA damage ( Blasiak et al, 2004 ). Consistently, oxidative damage and DNA strand breaks have been found in both type 1 and type 2 diabetic patients ( Goodarzi et al, 2010 ; Tatsch et al, 2012 ; Anand et al, 2014 ). We have recently shown in Drosophila that PLP deficiency can further increase DNA damage in cells from diabetic individuals ( Merigliano et al, 2018 ).…”
Section: Plp Depletion As New Cancer Risk Factor In Diabetic Cellssupporting
confidence: 52%
“…In this present investigation we observe an increased rate of sCA in diabetics with vascular complications as compared to diabetics without vascular complications and normal control individuals. This increased rate can be attributed to increased oxidative stress [41,42] as evidently shown in our study. The significantly high frequency of chromosomal aberrations among type 2 diabetics may therefore indicate that diabetes individuals can be at a higher risk of developing cancers than the control subjects (apparently healthy individuals).…”
Section: Discussionsupporting
confidence: 77%
“…However, this study noted a long standing poor glyceamic control (measured by HbA1c-glycated hemoglobin) as a prominent feature among diabetics especially among those with vascular complications and this goes a long way in accessing the effectiveness of compliance to therapy by patients. Evidently, invitro and in-vivo studies have shown that chronic hyperglycemic conditions (as observed in type 2 diabetes) is associated with decreased antioxidants and increase production of reactive oxygen (RO) and reactive nitrogen (RN) species which leads to nitrooxidative stress affecting biomolecules thereby adversely affecting the vascular (micro and or macro) body system and functioning [6,39,40] and also affecting genomic stability of an organism [41,42]. This study however, investigates the role of free radicals production on protein carbonylation, DNA damage and genomic instability among type 2 diabetes and its associated vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Study conducted by Okumura et al (2002) has demonstrated increased proliferation of breast cancer cells when subjected to elevated glucose concentration, linking the role of protein kinases and Peroxisome proliferatoractivated receptors. Another recent study (Anand et al, 2014) has found raised chromosomal abnormalities in diabetic subjects as compared to healthy controls, thus increasing he risk of cancer may be due to genomic instability.…”
Section: Introductionmentioning
confidence: 96%